NON-LINEAR IMPACT OF THE OFF-BALANCE SHEET ACTIVITIES TO BANK RISK - Pristanto Silalahi; Elok Pakaryaningsih (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
Banks face many restrictions on interest-based income under various regulatory requirements. These conditions provide banks with space to seek alternative income through fee-based activities and are considered to increase banking profitability. The main problem is moral hazard: OBS activities become excessive. This study tested the effect and modelled the non-linear relationship between off-balance sheet banking activity and bank risk using data on large and small banks in Indonesia. Its result confirms that there is a non-linear relationship between OBS and risk. The main implication is that not all OBS activities affect bank risk. What is interesting in our findings is the direction of OBS's influence on bank risk, which has so far been viewed from two perspectives and two conditions: positive and negative. The results also show that each OBS instrument can, of course, have both positive and negative effects on bank risk (concave and convex), depending very much on the bank's size. Finally, it indicates that small-capitalization banks are more sensitive to bank risk than large-capitalization banks.